A Microfluidic In Vitro Three-Dimensional Dynamic Model of the Blood–Brain Barrier to Study the Transmigration of Immune Cells - Megha Meena; Robin Vandormael; Maxime De Laere; Isabel Pintelon; Zwi Berneman; Regan Watts; Nathalie Cools (Brain Sciences, 2022)
To study the biodistribution of new chemical and biological entities, an in vitro model of the blood–brain barrier (BBB) may become an essential tool during early phases of drug discovery. Here, we present a proof-of-concept of an in-house designed three-dimensional BBB biochip designed by us. This three-dimensional dynamic BBB model consists of endothelial cells and astrocytes, co-cultured on opposing sides of a polymer-coated membrane under flow mimicking blood flow. Our results demonstrate a highly effective BBB as evidenced by (i) a 30-fold increase in transendothelial electrical resistance (TEER), (ii) a significantly higher expression of tight junction proteins, and (iii) the low FITC–dextran permeability of our technical solution as compared to a static in vitro BBB model. Importantly, our three-dimensional BBB model effectively expresses P-glycoprotein (Pg-p), a hallmark characteristic for brain-derived endothelial cells. In conclusion, we provide here a complete holistic approach and insight to the whole BBB system, potentially delivering translational significance in the clinical and pharmaceutical arenas.